2007
DOI: 10.1016/j.bbadis.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fas expression by RNAi modulates 5-fluorouracil-induced apoptosis in HCT116 cells expressing wild-type p53

Abstract: Drug resistance to 5-fluorouracil (5-FU) is still a major limitation to its clinical use. In addition, the clinical value of p53 as a predictive marker for 5-FU-based chemotherapy remains a matter of debate. Here, we used HCT116 human colorectal cancer cells expressing wild-type p53 and investigated whether inhibition of Fas expression by interference RNA modulates 5-FU-induced apoptosis. Cells were treated with 5-FU (1, 4 or 8 microM) for 8-48 h. Cell viability was evaluated by trypan blue dye exclusion. Apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 39 publications
3
51
0
Order By: Relevance
“…7 Several studies have demonstrated that 5-FU elicits apoptosis in colon cancer cells through the activation of intracellular caspases such as caspase-3, 8 and 9. 5 However, there is no conclusive evidence supporting the involvement of caspase-6 activation in 5-FU-evoked apoptosis of colon cancer cells, despite it being a possible major signalling event in colon cancer cell apoptosis. 6 In this study, we showed that 5-FU triggered the cancer cell apoptosis through the activation of caspase-6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Several studies have demonstrated that 5-FU elicits apoptosis in colon cancer cells through the activation of intracellular caspases such as caspase-3, 8 and 9. 5 However, there is no conclusive evidence supporting the involvement of caspase-6 activation in 5-FU-evoked apoptosis of colon cancer cells, despite it being a possible major signalling event in colon cancer cell apoptosis. 6 In this study, we showed that 5-FU triggered the cancer cell apoptosis through the activation of caspase-6.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite advancements in treatment regimens since the inception of 5-FU more than 40 years ago, response rates of colon cancer chemotherapy remain as low as 10-20%, and tumor cell resistance persists as a significant limitation to the clinical use of 5-FU. 5-FU has been shown to inhibit DNA proliferation in colon cancer cells by inhibiting the enzyme thymidylate synthase, leading to apoptosis, 3 a mechanism of active cell death characterized by rapid loss of plasma membrane integrity, DNA fragmentation, and altered expression of numerous genes. 4 Specifically, 5-FU has been shown to cause DNA damage-induced apoptosis in colon cancer cells through expression of Fas ligand and increase in cell surface expression of Fas, triggering the death receptor pathway of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as shown by immunostaining, in response to 5-FU, both TNF-family receptors DR5 and CD95 are accumulated in the plasma membrane (Figure 1a), indicating that either one of them or both could have a vital role for efficient apoptosis. As conflicting evidences exist in this matter, 12,13,17 we decided to assess the contribution of each individual receptor to initiator caspase-8 and effector caspase-3 activation by means of small interfering RNA (siRNA) technology (Figures 1b and c). This experimental approach clearly demonstrated that DR5 but not CD95 is the sole receptor required for caspase-8 activation and further processing of caspase-2 and effector caspase-3 upon treatment with 5-FU.…”
Section: Dr5mentioning
confidence: 99%
“…11 Similar data have been provided by using tumor cell lines, although conflicting evidences exist postulating DR4, DR5 or CD95 as the regulatory receptor for caspase-8 activation and apoptosis. [12][13][14] Interestingly, death receptor ligand does not seem to be required for DISC formation in this particular apoptosis pathway. 12 Most DR5 expression studies in clinical tumor sections do not experimentally verify whether the death receptor is induced as a consequence of chemotherapy, or if it is a response to tumorogenesis.…”
mentioning
confidence: 92%